2020
DOI: 10.47067/ramss.v3i3.69
|View full text |Cite
|
Sign up to set email alerts
|

An Econometric Analysis of Exigent Determinants of Trade Balance in Finland: An Autoregressive Distributed Lag (ARDL) Approach

Abstract: A number of research papers analyzed the factors that may have impacts on the balance of trade for the effective macroeconomic policies but the results of these studies have created ambiguity which implies that further research is needed as the worsening trade balance can limit the economic growth of any country. Hence the current paper is an effort to study the short-run and long-run relationships among trade balance, real effective exchange rate, GDP per capita, urbanization, unemployment and inflation rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…ARDL is an econometric testing tool that assumes that the variables studied will affect the variables themselves in the previous year [2]. The stages of testing the ARDL are the same as the ECM model test, which lies in analysing the data stationarity test, the optimal lag test, the cointegration test, and ARDL linear regression [10]. The optimal lag length used for regression estimation is based on the stationarity level criteria [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ARDL is an econometric testing tool that assumes that the variables studied will affect the variables themselves in the previous year [2]. The stages of testing the ARDL are the same as the ECM model test, which lies in analysing the data stationarity test, the optimal lag test, the cointegration test, and ARDL linear regression [10]. The optimal lag length used for regression estimation is based on the stationarity level criteria [2].…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variable data in this research is the level of CPO export. Testing the estimation of the ARDL and ECM models analyzes the long-term and short-term equations between the relationship between the independent and dependent variables [2], [10], [16]. Before determining the selection of ARDL and ECM models, a step testing process is needed, namely the unit root test (stationarity) [11].…”
Section: Selection Of the Ardl And Ecm Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study [17] focused on analyzing factors that affect Finland's trade balance using the ARDL methodology, aiming to investigate the short-term and long-term relationships between the trade balance, real effective exchange rate, GDP per capita, urbanization, unemployment, and inflation rate in the Finnish economy. It was found that the real effective exchange rate, urbanization, and inflation significantly and negatively impact Finland's trade balance in both the short and long term.…”
Section: Ardl Technique Application and Studies In Finlandmentioning
confidence: 99%
“…The empirical findings of the study of Ditta et al (2020) on the determinants of Finland's trade balance showed that the real effective exchange rate, urbanization, and inflation have a significant but negative impact on Finland's trade balance in both the short and the long run, while GDP per capita and unemployment have a significant but positive impact. The absence of any structural break in the model is confirmed by the plots of recursive estimates on both CUSUM and CUSUM square.…”
Section: Literature Reviewmentioning
confidence: 99%